Sensitivity of Clarireedia spp. to benzimidazoles and dimethyl inhibitors fungicides and efficacy of biofungicides on dollar spot of warm season turfgrass - Ghimire, Bikash; Aktaruzzaman, Md.; Chowdhury, Shukti R.; Spratling, Willis T.; Vermeer, C. Brian; Buck, James W.; Martinez-Espinoza, Alfredo D.; Bahri, Bochra A. (Frontiers in Plant Science, 2023)
Dollar spot caused by Clarireedia spp. (formerly Sclerotinia homoeocarpa) is an economically destructive fungal disease of turfgrass that can significantly compromise turf quality, playability, and aesthetic value. Fungicides are frequently used to manage the disease but are costly and potentially unfavorable to the environment. Repeated use of some active ingredients has resulted in reduced efficacy on C. jacksonii causing dollar spot in cool-season turfgrasses in the US. Experiments were conducted to study fungicide sensitivity of Clarireedia spp. as well as to develop alternatives to fungicides against dollar spot on warm-season turfgrass in Georgia. First, 79 isolates of Clarireedia spp. collected across the state were tested on fungicide-amended agar plates for their sensitivity to thiophanate-methyl (benzimidazole) and propiconazole (dimethyl inhibitor). Seventy-seven isolates (97.5%) were sensitive (0.001 to 0.654 μg/mL) and two isolates (2.5%) were found resistant (>1000 μg/mL) to thiophanate-methyl. However, in the case of propiconazole, 27 isolates (34.2%) were sensitive (0.005 to 0.098 μg/mL) while 52 isolates (65.8%) were resistant (0.101 to 3.820 μg/mL). Next, the efficacy of three bio- and six synthetic fungicides and ten different combinations were tested in vitro against C. monteithiana. Seven bio- and synthetic fungicide spray programs comprising Bacillus subtilis QST713 and propiconazole were further tested, either alone or in a tank mix in a reduced rate, on dollar spot infected bermudagrass ‘TifTuf’ in growth chamber and field environments. These fungicides were selected as they were found to significantly reduce pathogen growth up to 100% on in vitro assays. The most effective spray program in growth chamber assays was 100% B. subtilis QST713 in rotation with 75% B. subtilis QST713 + 25% propiconazole tank mix applied every 14 days. However, the stand-alone application of the biofungicide B. subtilis QST713 every seven days was an effective alternative and equally efficacious as propiconazole, suppressing dollar spot severity and AUDPC up to 75%, while resulting in acceptable turf quality (>7.0) in field experiments. Our study suggests that increased resistance of Clarireedia spp. to benzimidazoles and dimethyl inhibitors warrants continuous surveillance and that biofungicides hold promise to complement synthetic fungicides in an efficacious and environmentally friendly disease management program.